Kajian Integrasi Islam dan Sains pada Pendayagunaan Besi Oksida dalam Bidang Medis - Aprilia Dewi Ardiyanti (Kaunia: Integration and Interconnection Islam and Science Journal, 2022)
Al-Qur’an as a guide for Muslims is a source of knowledge. There are scientific clues that are summarized in the verses of the kauniyah. One of the topics discussed is about iron in Surah Al-Hadid verse 25. In this verse, it is explained about the origin of iron, its strength, and its benefits for humans. The analysis and explanation of the verse were carried out using a qualitative method of literature study. The results show that the origin of iron comes from nuclear fusion reactions of stars then explode and fall to earth via meteors. The uses of iron cover various lines of life, especially when it is reduced to nanometers in size. One example is an iron oxide from the iron sand which is used as a medium for drug delivery systems and cancer hyperthermia therapy. The correlation and suitability of the information from the Qur’an with the results of the study show a confirmative and integrated relationship.